Gender, Judaism, and Bourgeois Culture in Germany, 1800-1870 - Baader, Benjamin Maria (Book collections on Project MUSE., 2006)
In this study of gender and religious culture, Benjamin Maria Baader explores the transformation of Judaism during a period of profound change in 19th century Germany.